2014
DOI: 10.1097/qai.0000000000000044
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors for Incident Hepatitis C Infection Among Men Who Have Sex With Men With HIV-1 Infection in a Large Urban HIV Clinic in Tokyo

Abstract: Incident HCV infection is increasing among HIV-1-infected MSM noninjection drug users at resource-rich setting in Asia. Illicit drug use is an independent risk factor for incident HCV infection in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
51
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 28 publications
8
51
2
Order By: Relevance
“…Data from 3014 HIV-infected MSM from 12 cohorts within the Concerted Action on SeroConversion to AIDS and Death in Europe (CASCADE) collaboration showed that the HCV incidence increased from 0.55-0.81/100 PY in 1995 to 2.34-5.11/100 PY in 2007 [76]. Similar rises were observed among HIV-infected MSM in North America, Australia, and Asia [63,75,77,79,80]. One phylogenetic analysis revealed a large Europeanwide network of HCV transmission among HIVinfected MSM coinciding with the introduction of combination antiretroviral therapy and associated increases in sexual risk behaviours [82].…”
Section: Incidence Of Hcv Infectionsupporting
confidence: 73%
See 1 more Smart Citation
“…Data from 3014 HIV-infected MSM from 12 cohorts within the Concerted Action on SeroConversion to AIDS and Death in Europe (CASCADE) collaboration showed that the HCV incidence increased from 0.55-0.81/100 PY in 1995 to 2.34-5.11/100 PY in 2007 [76]. Similar rises were observed among HIV-infected MSM in North America, Australia, and Asia [63,75,77,79,80]. One phylogenetic analysis revealed a large Europeanwide network of HCV transmission among HIVinfected MSM coinciding with the introduction of combination antiretroviral therapy and associated increases in sexual risk behaviours [82].…”
Section: Incidence Of Hcv Infectionsupporting
confidence: 73%
“…Beginning in 2004, an increase in the incidence of acute HCV infection was reported among HIVinfected MSM in Europe, North America, Australia, and Asia [60,[63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80]11,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. A systematic review of these studies found that the incidence of acute HCV from 2000-2012 was approximately four times higher in HIV-positive MSM (0.61/100 PY) than HIVnegative MSM (0.15/100 PY) [81].…”
Section: Incidence Of Hcv Infectionmentioning
confidence: 99%
“…Infections in HIV-infected individuals were predominately due to genotype 1a viruses and found only in males possibly reflecting un-reported sex between men. In addition to drug use, the observation of transmission in known HIV positives is not surprising with recent studies from high income countries have demonstrated a high incidence of recent HCV infections in HIV-infected MSMs [8,18,23,[25][26][27][29][30][31][33][34][35][36]. Recent PHE data demonstrated a 21% increase in new HIV infections amongst MSMs in London since 2011 [20].…”
Section: Discussionmentioning
confidence: 93%
“…Among 1182 HIV-positive men, a clinic-based study in Japan reported an HCV incidence of 7.9 and 40.0 per 1000 person-years in non-IDUs and IDUs, respectively. 31 The large-scale Multicenter AIDS Cohort in the US reported an HCV incidence of 1.6 per 1000 person-years in non-IDUs, and this was significantly higher in previous and current IDUs (6.9 and 25.8 per 1000 person-years, respectively). 32 In Melbourne, Australia, 620 HIV-positive men were followed up for a total of 4359 person-years, and the incidence of HCV was significantly higher in IDUs (hazard ratio = 8.7, 95% CI 4.6-16.6).…”
Section: Injecting Drug Use As a Risk Factormentioning
confidence: 99%